1989
DOI: 10.1161/01.hyp.14.6.652
|View full text |Cite
|
Sign up to set email alerts
|

Long-term inhibition of angiotensin converting enzyme suppresses calcium channel agonist-induced contraction of aorta in hypertensive rats.

Abstract: To elucidate functional changes in the vascular smooth muscle of spontaneously hypertensive rats (SHR) after chronic inhibition of angiotensin converting enzyme, we examined the contractile responses to different pharmacological interventions in the isolated aortas from SHR treated with a novel angiotensin converting enzyme inhibitor, CS-622 (10 mg/kg/day) for 20 weeks. In normal K + medium, a marked contraction was elicited by increasing Ca 2+concentration from 0 to 3 mM in aortas from a control group of SHR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

1990
1990
1998
1998

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 32 publications
2
7
1
Order By: Relevance
“…40 Our previous studies showed that long-term administration of CS-622 suppressed the increased Ca 2+ -dependent resting tone and CGP-28392-induced contraction in SHR aorta and that these suppressions were never achieved by either long-term treatment with hydralazine or acute inhibition of aortic ACE in vitro. 15 - 35 In the present study, long-term treatment with CS-622 (10 mg/kg/ day) lowered blood pressure of SHR to the same level as that of WKY rats (Table 1) and lowered both [Ca 2+ ], and resting tone in SHR aortas to levels in WKY rat aortas (Figure 2). Exaggerated response of SHR aortas in [Ca 2+ ]j and tension development in response to CGP-28392 was also normalized by chronic inhibition of ACE.…”
Section: Effects Of Nicardipine On Basal Calcium Level and Basal Tenssupporting
confidence: 61%
“…40 Our previous studies showed that long-term administration of CS-622 suppressed the increased Ca 2+ -dependent resting tone and CGP-28392-induced contraction in SHR aorta and that these suppressions were never achieved by either long-term treatment with hydralazine or acute inhibition of aortic ACE in vitro. 15 - 35 In the present study, long-term treatment with CS-622 (10 mg/kg/ day) lowered blood pressure of SHR to the same level as that of WKY rats (Table 1) and lowered both [Ca 2+ ], and resting tone in SHR aortas to levels in WKY rat aortas (Figure 2). Exaggerated response of SHR aortas in [Ca 2+ ]j and tension development in response to CGP-28392 was also normalized by chronic inhibition of ACE.…”
Section: Effects Of Nicardipine On Basal Calcium Level and Basal Tenssupporting
confidence: 61%
“…The aortic smooth muscles of spontaneously hypertensive rats, however, have the active tone (Noon et al, 1978;Lindner and Heinle, 1987;Fitzpatrick and Szentivanyi, 1980 ;Sada et al, 1989 ;Sunano et al, 1992 ;Sasaki et al, 1993 ;Sunano et al, 1996). The active tone of these smooth muscles are sensitive to extracellular Ca2+ and abolished by the removal of Ca2+ from incuba tion medium or by the application of Ca antagonists Sada et al, 1989 ;Fitzpatrick and Szentivanyi, 1980 ;Lindner and Heinle, 1987 ;Noon et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…In the spontaneously hypertensive rats, however, it has been known that the aortic smooth muscle exhibits the active tone (Sada et al, 1989 ;Fitzpatrick and Szentivanyi, 1980 ;Lindner and Heinle, 1987 ;Noon et al, 1978 ;Sunano et al, 1992 ;Sasaki et al, 1993 ;Sunano et al, 1996). We have observed using various strains of spontaneously hypertensive rats that the amplitude of the active tone of aorta became greater as the blood pressure of the rats increased (Sasaki et al, 1993 ;Sunano et al,1996).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several investigators also reported that voltage-dependent Ca channels are altered in the vascular smooth muscle of SHR (36)(37)(38). There are also several reports that suggest that there is a defect of SR Ca uptake or release in vascular smooth muscle of SHR (39-42).…”
Section: Contraction Experimentsmentioning
confidence: 96%